Cell type-dependent integrin distribution in adhesion and migration responses on protein-coated microgrooved substrates - Sales Ramos, Adrià; Spatz, Joachim P. (ACS omega, 2019)
Although integrins are responsible for the interaction of cells with their environment, e.g., the extracellular matrix or artificial substrates, there is still a lack of knowledge about their role in cell adhesion and migration on protein-coated substrates with microtopography. Understanding such interactions could lead to new applications in e.g., medical implants as well as shed light on processes such as embryonic development, angiogenesis, wound healing, and tumor progression. In this work, the influence of surface topography and chemistry on αvβ3 and α5β1 integrin-mediated cell adhesion and migration of healthy and malignant human cell types (human coronary artery endothelial cells, human osteosarcoma cells, and human skin fibroblasts cells) was studied, using microgrooved and flat substrates covered by two different extracellular proteins, fibronectin and vitronectin. Although some general behaviors can be observed, cell migration (speed, directionality, and persistence time) and morphological adaptation (cell area, aspect ratio, and circularity) of cells on protein-coated microgrooved substrates are mainly dependent on the cell type and its specific integrin expression.